What Did We Learn? : The Shelter Response and Housing Recovery in the First Two Years after the 2010 Haiti Earthquake - World Bank (World Bank, Washington, DC, 2017)
The response to the January 2010 Haiti earthquake has been in the spotlight ever since the disaster, and a significant number of evaluations and analyses have been disseminated in the years since. This report is intended to help housing and shelter practitioners improve future post-disaster shelter responses and housing recovery programs and the integration between them. The report covers the shelter and housing responses in Haiti, and looks especially at how early decisions about sheltering affected the housing response. The analysis also covers other interrelated topics that heavily affected work on shelter and housing: disaster risk management (DRM), the urban context, and recovery financing.